1986
DOI: 10.1007/bf02907322
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence polymorphisms in the genus saccharomyces III. Restriction endonuclease fragment patterns of chromosomal regions in brewing and other yeast strains

Abstract: 30 bottom fermenting strains, 13 hybrid lager strains, 11 top fermenting strains. In addition, 24 other yeast species and strains have been analysed in this study. Four DNA regions have been monitored by restriction endonuclease fragment pattern polymorphisms. The regions analysed are: RDN1 (encoding cytosolic ribosomal RNA molecules) located on chromosome XII in S. cerevisiae, HIS4 (histidine 4) and LEU2 (leucine 2) both located on chromosome III and the Ty elements which are distributed at different position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 51 publications
2
50
0
Order By: Relevance
“…Strains B and C differ by their Ty element patterns. B (Carlsberg lager strain) contains pattern I, while C (Danish lager strain BK2208) contains pattern IIa (27).…”
Section: S Bayanusmentioning
confidence: 99%
See 3 more Smart Citations
“…Strains B and C differ by their Ty element patterns. B (Carlsberg lager strain) contains pattern I, while C (Danish lager strain BK2208) contains pattern IIa (27).…”
Section: S Bayanusmentioning
confidence: 99%
“…DNA preparations for OFAGE separations were made according to SCHWARTZ and CANTOR (31), with the modifications reported by PEDERSEN (27). The apparatus was constructed after the descriptions of CARLE and OLSON (5, 6).…”
Section: Preparation Of D N Amentioning
confidence: 99%
See 2 more Smart Citations
“…The use of a single-chromosome transfer of chromosomes III, V, X, XII and XIII from the Carlsberg lager production yeast 244 to a haploid S. cerevisiae strain by cytoduction revealed at least two divergent genomes in S. carlsbergensis, one of which is derived from S. cerevisiae, while the origin of the second genome is less clear (Nilsson-Tillgren et al, 1983;Kielland-Brandt et al, 1995;Andersen et al, 1999). Based on the Southern hybridization experiments and sequencing of some non-S. cerevisiae genes, another brewing yeast S. monacensis CBS 1503 was proposed to be a second parent of the lager brewing yeast S. carlsbergensis (Pedersen, 1986;Hansen and Kielland-Brandt, 1994;Børsting et al, 1997). However, recent PCR and genetic analyses of single chromosomes showed that S. monacensis itself is an incomplete hybrid containing a part of the S. cerevisiae genome (Andersen et al, 1999).…”
Section: Introductionmentioning
confidence: 99%